A BIOCHEMICAL AND HISTOPATHOLOGIC STUDY SHOWING PROTECTION AND TREATMENT OF GENTAMICIN-INDUCED NEPHROTOXICITY IN RABBITS USING VITAMIN C - Rehman, K; Akash, M S H; Azhar, S; Khan, S A; Abid, R; Waseem, A; Murtaza, G; Sherazi, T A (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Gentamicin and vitamin C have been proposed as nephrotoxic and antioxidant, respectively. This study involved biochemical and histopathologic investigation showing protection and treatment of gentamicin-induced nephrotoxicity in rabbits using vitamin C for 26 days hypothesizing that whether vitamin C would inhibit or decrease the raised serum urea and creatinine levels. This study was conducted on 25 healthy male albino rabbits (average weight 1.5±0.2 kg), classified into 5 groups: group A, B, C, D and E for nephrocurative (study-I) and nephroprotective (study-II) studies. Control group of rabbits (group A) received only the vehicle of gentamicin ampoule. In study-I, gentamicin sulphate (GS 80 mg/kg, i.m.) was administered to group B and C rabbits for ten days, then group C rabbits received vitamin C 250 mg/Kg for remaining 16 days. Group D and E received GS 80 mg/kg and GS 80 mg/kg i.m.-vitamin C 250 mg/kg orally, respectively during whole period (26 days) of study-II. After 26 days, various biochemical parameters, i.e. serum creatinine, blood urea nitrogen (BUN), and serum antioxidant activity, and histopathologic investigations were made. Nephrotoxicity was observed in rabbit groups B, C and D as evident from significant (p<0.05) high levels of serum creatinine and BUN and low serum antioxidant levels as compared to the levels of control group. Decrease in the levels of serum creatinine and BUN along with the increase in serum antioxidant activity was observed after vitamin C treatment in group C. While, renal-protective role of vitamin C was seen in group E as compared to the control. In conclusion, Gentamicin induced nephrotoxicity can be attenuated or treated using vitamin C.